“JUVENILE REHABILITATION” - JUVENILE JUSTICE SYSTEM - Vasan, Praveen (International Journal of Psychosocial Rehabilitation, 2020)
The problem of juvenile delinquency is not new, it occurs in all societies simple as well as complex, that is, wherever and whenever a relationship is affected between a group of individuals leading to maladjustments and conflicts...More than a century ago, Abraham Lincoln had said: “A child is a person who is going to carry on what you have started. He is going to sit where you are sitting, and when you are gone, attend to those things you think are important. You may adopt all the policies you please, but how they are carried out depends on him. He is going to move in and take over your churches, schools, universities and corporations.Considering the magnitude of thisproblem and issues involved, analysis indicates that the number of factors for neglect and delinquency are mostly common and interrelated, based on socio-economic and psychological reasons. Poverty, broken homes, family tensions, emotional abuse, rural-urban migration, break-down of social values and joint family system, atrocities and abuses by parents or guardians, faulty educational system, the influence of media besides the unhealthy living conditions of slums and such other conditions explain the phenomena of juvenile delinquency. The neglect of children by their parents, family, society and the nation create detrimental effect on their physical, mental growth and over all development. Needless to say that most of the factors causing delinquency are in plenty in the Indian context and any attempt to prevent and control them can be fruitful for society. After all, the children represent the nation and the coming future of the country. Even international instance like UN Standard Minimum Rules for the Administration of Juvenile Justice, also known as Beijing Rules, 1985 and UN Convention on the Rights of Child, 1989, are notable and has articulated the global consensus on giving special attention to the children who come in conflict with law. In the above context, this paper tries to highlight the growth and development of juvenile justice system in India, further, take a brief look at constitutional provisions, Juvenile justice Act, 2015 andextent of delinquency in India.Juvenile delinquency is an aspect of society that has started demanding greater attention in the recent years. The very many changes in societal standards, the increase in awareness among youth as compared to the youth of yesteryears, the access to multitudes of informationJuvenile Delinquency Rehabilitation or Punishment.